Molecular cellular microbiology - Sansonetti, P. J.; Zychlinsky, Arturo (Methods in microbiology, 2002)
This volume in the Methods in Microbiology series focuses on the interaction of microorganisms and the host cell, presenting detailed experimental techniques for modern microbiological research. The book focuses on current technical methods, including imaging technologies, cellular biochemistry, and the establishment and exploitation of cell assay systems. Also covered are methods for studying gene expression and detecting virulence genes. By studying the major techniques used to study cross talk between microbes and cells, rather than just presenting systems, this book distinguishes itself as an essential guide for all researchers working in microbiology, cell biology, and immunology.